Ursolic acid: biological functions and application in animal husbandry - Liu, Guanhui; Qin, Peng; Cheng, Xinying; Wu, Lifei; Wang, Ruoning; Gao, Wei (Frontiers in Veterinary Science, 2023)
Ursolic acid (UA) is a plant-derived pentacyclic triterpenoid with 30 carbon atoms. UA has antiinflammatory, antioxidative, antimicrobial, hepato-protective, anticancer, and other biological activities. Most studies on the biological functions of UA have been performed in mammalian cell (in vitro) and rodent (in vivo) models. UA is used in animal husbandry as an antiinflammatory and antiviral agent, as well as for enhancing the integrity of the intestinal barrier.Although UA has been shown to have significant in vitro bacteriostatic effects, it is rarely used in animal nutrition. The use of UA as a substitute for oral antibiotics or as a novel feed additive in animal husbandry should be considered. This review summarizes the available data on the biological functions of UA and its applications in animal husbandry.